Health Promoting Behaviours among Adolescents in a School of Rupendehi, Nepal - Kachapati, Anuja; Thapa, Bhagawati; Rawal, Shristee; Bhattarai, Sigma; Chhetri, Pradip (Med Phoenix, 2025)
Introduction: Health promoting behavior is a multidimensional and spontaneous behavior and perception of individual that includes actions and perceptions aimed at maintaining or improving health, enhancing quality of life, self-actualization and self-satisfaction. During adolescence, rapid physical and physiological changes increase the need for effective health promotion measures to maintain optimal well-being. The major causes of morbidity and mortality in adolescence are not diseases themselves but health damaging behaviors. This study aimed to assess the health promoting behaviors among adolescents in a school setting. Materials and methods: A cross sectional study was conducted to assess the health promoting behaviors among adolescents from 15th June to 15th September, 2025. Ethical approval was obtained from the Institutional Review Committee. Out of 160 adolescent students, 114 were selected using probability computer generated simple random sampling technique. A validated self-administered validated questionnaire, the Adolescents Health Promotion Short Form Scale (AHPSS) was used after obtaining permission with author via mail. Data were analyzed by using descriptive and inferential statistics with SPSS version 16. Results: The findings of the study showed that 50.90% of respondents had good level of health promoting behaviors. Mean score of each domain were, nutrition was 16.53±4.88, social support was 24.86±5.77, health responsibility was 28.50±5.37, life appreciation was 34.56±4.90, exercise16.53±4.88, and stress management 23.19±4.36 respectively. Nutrition, social support, life appreciation, and exercise scores were significantly higher among males compared to females. Conclusion: The study concludes that adolescents demonstrated generally good health promoting behaviors. There was a significant association between the level of health promoting behaviors and gender, mothers’ and fathers’ educational status. Nutrition, social support, life appreciation, and exercise scores were all significantly higher among males than females.